2022
DOI: 10.1186/s12934-022-01829-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of pediocin/papA in Bacillus subtilis

Abstract: Listeria monocytogenes is a food-borne pathogen. Pediocin is a group IIα bacteriocin with anti-listeria activity that is naturally produced by Pediococcus acidilactic and Lactobacillus plantarum. The pedA/papA gene encodes pediocin/plantaricin. In native hosts, the expression and secretion of active PedA/PapA protein rely on the accessory protein PedC/PapC and ABC transporter PedD/PapD on the same operon. The excretion machines were also necessary for pediocin protein expression in heterologous hosts of E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…6 Benchmarking of microbial pediocin PA-1 production in natural and recombinant cell factories. The data show previous efforts (from top to bottom in the upper part) using L. lactis CL1 [ 107 ], B. subtilis [ 108 ], P. acidilactici 347 [ 109 ], E. coli producing the M31L version of the peptide [ 110 ], P. acidilactici 347 [ 111 ], C. glutamicum CR099 pXMJ19 P tac pedACD Cg [ 23 ], and P. acidilactici 1521 [ 112 ] in shake flasks and test tubes. In addition, the results of the optimization from this work are shown, using C. glutamicum CR099 pXMJ19 P tac pedACD Cg .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…6 Benchmarking of microbial pediocin PA-1 production in natural and recombinant cell factories. The data show previous efforts (from top to bottom in the upper part) using L. lactis CL1 [ 107 ], B. subtilis [ 108 ], P. acidilactici 347 [ 109 ], E. coli producing the M31L version of the peptide [ 110 ], P. acidilactici 347 [ 111 ], C. glutamicum CR099 pXMJ19 P tac pedACD Cg [ 23 ], and P. acidilactici 1521 [ 112 ] in shake flasks and test tubes. In addition, the results of the optimization from this work are shown, using C. glutamicum CR099 pXMJ19 P tac pedACD Cg .…”
Section: Discussionmentioning
confidence: 86%
“…The medium of the letter additionally contained 2 mM IPTG. The pediocin PA-1 concentration obtained with B. subtilis was estimated from the reported biological activity [ 108 ] using the recently obtained conversion factor [ 23 ] …”
Section: Discussionmentioning
confidence: 99%
“…The pediocin produced in B. subtilis showed similar thermotolerant properties as reported in previous studies. 148,181,182 Rhizocticins are antifungal phosphonate oligopeptide antibiotics produced by B. subtilis ATCC 6633 (Table 1). 149,183 These antibiotics consist of di-and tripeptides with the unique nonproteinogenic amino acid (Z)-L-2-amino-5-phosphono-3-pentenoic acid (APPA) at their C-terminus.…”
Section: Other Bioactive Natural Productsmentioning
confidence: 99%
“…170,171 Heterologous production of this bacteriocin has been achieved in various hosts, such as E. coli, 172,173 Lactobacillus lactis, 174,175 and Corynebacterium glutamicum. 176 A study by Wang et al investigated if the pediocin peptide (PapA) could be heterologously produced in B. subtilis WB800N and secreted without the need for accessory protein PedC/PapC and ABC transporter PedD/PapD, as previous research had shown that these proteins impose a metabolic burden to the host 148,176 (Table 1). The study used a shuttle vector to express both the original and a codon-optimized version of the papA gene as a fusion protein with an a-amylase signal peptide for secretion.…”
Section: Other Bioactive Natural Productsmentioning
confidence: 99%
“…Bacillus subtilis , similar to C. glutamicum , exhibits remarkable secretory characteristics and possesses a well-established fermentation process and genetic manipulation techniques. Currently, active bacteriocin expression in B. subtilis has also been successfully achieved by Li et al [ 34 ]. In that study, the structural gene encoding mature pediocin PA-1 was connected with vector pHT43 and then introduced into B. subtilis WB800N.…”
Section: The Production Of Class Iia Bacteriocins By Different Cell F...mentioning
confidence: 99%